Freedom of expression and hate speech regarding the activities of public officials in political debate - Stępień-Załucka, Beata (Ius Novum, 2024)
Freedom of expression has accompanied humanity for centuries. As societies have developed over the decades, it has evolved and changed. In parallel, the brutalisation of language has also progressed, leading to the emergence of hate speech. Today, hate speech is a global phenomenon, significantly impacting the speech of public figures. This is due to the fact that such statements reach a wide audience, which includes both supporters and opponents of such a person. Consequently, this leads to a wide-ranging debate where individual arguments lose relevance, overshadowed by the repetition of negative slogans and comments with hateful overtones. This article aims to delineate the boundary between freedom of expression and hate speech, highlighting the consequences associated with the use of hate speech by public figures. It seeks to prove the main thesis that hate speech in the activity of public figures is an unquestionably negative phenomenon and thus cannot benefit from the protection guaranteed under freedom of speech. Additionally, it posits that hate speech undermines the dignity of individuals and society, leads to a decline in the culture of speech, and diminishes both political and social culture. Consequently, it erodes the authority of public figures and harms the offices they hold by undermining trust in them.